Vibration Control of Magnetorheological Elastomer Beam Sandwich - Gigih Priyandoko; Tedi Kurniawan; Saffirna Mohd Soffie (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
A Magnetorheological Elastomer (MRE) is a smart material and that could change their properties by exposure to stimuli such as electric and magnetic fields, stress moisture and temperature. Objective of this research is to develop a MRE as vibration isolator of a beam sandwich under different currents to get different stiffness of the MRE. A MRE was fabricated by mixing silicon rubber, silicon oil and carbonyl iron particles together and then cured for 24 hours in a circular mold. Experimental result shows that that there were decreases in amplitude of the vibration in time and frequency domains when the current applied to the coil is increased.